Manajemen Kelas dalam Meningkatkan Efektifitas Proses Belajar Mengajar di Kelas XI SMP IT Al Mawaddah Warrahmah Kolaka - Taufik Ismail; Suhra Suhra (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Education is a procedure. Because, this affects everyone at some point in their lives. The interaction between individuals and their environment is what leads to the learning process. Thus, education can take place anywhere and at any time. Even though what is actually happening in the field is still critical because it has not yet achieved the expected level of success. Therefore, there are several aspects that a teacher needs to pay attention to in order to increase learning effectiveness. With the existing problems, it can be said that classroom management is a solution in the act of organizing or managing something so that it can run smoothly, successfully and efficiently. In teaching and learning activities, students need something that allows them to communicate effectively with each other, with the teacher, with other students, with the environment, with teaching materials, and with themselves. Therefore the aim of classroom management is to create a favorable classroom environment where each student can perform to the best of his ability.